1991
DOI: 10.1136/gut.32.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of postprandial mesenteric blood flow in humans: evidence for a cholinergic nervous reflex.

Abstract: The primary objectives of this study were to assess the physiological importance of postprandial blood concentrations of cholecystokinin octapeptide (CCK8), secretin, gastrin 17, and glucagon on superior mesenteric artery blood flow and to determine whether a nervous reflex mechanism is involved in postprandial mesenteric artery blood flow in healthy humans. The superior mesenteric artery was chosen to assess intestinal blood flow because it supplies a large part of the small intestine, the right colon, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
60
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 32 publications
(4 reference statements)
8
60
2
Order By: Relevance
“…In mammalian studies, peptide dosages that stimulated vascular response were much greater than endogenous levels (Premen et al, 1985;Matheson et al, 2000). The fact that dosages administered at physiological levels failed to induce gastrointestinal vasodilation or increase in blood flow calls into question whether any of these peptides are involved in the postprandial regulation of gastrointestinal blood flow (Sieber et al, 1991;Matheson et al, 2000). Two pieces of evidence suggesting humoral modulation of gut blood flow originate from studies on the ball python, Python regius.…”
Section: Mechanisms Underlying Gastrointestinal Hyperemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian studies, peptide dosages that stimulated vascular response were much greater than endogenous levels (Premen et al, 1985;Matheson et al, 2000). The fact that dosages administered at physiological levels failed to induce gastrointestinal vasodilation or increase in blood flow calls into question whether any of these peptides are involved in the postprandial regulation of gastrointestinal blood flow (Sieber et al, 1991;Matheson et al, 2000). Two pieces of evidence suggesting humoral modulation of gut blood flow originate from studies on the ball python, Python regius.…”
Section: Mechanisms Underlying Gastrointestinal Hyperemiamentioning
confidence: 99%
“…Although the small intestine is richly innervated by sympathetic and parasympathetic fibers, it is not clear what the role of the enteric nervous system is in moderating postprandial hyperemia (Sieber et al, 1991;Matheson et al, 2000). Originally it was suggested that cholinergic mechanisms were responsible for intestinal vasodilation (Secor and Diamond, 1997a;Secor and Diamond, 1997b).…”
Section: Mechanisms Underlying Gastrointestinal Hyperemiamentioning
confidence: 99%
“…Food is a very potent hyperemic stimulus in the splanchnic vascular area, both in normal subjects, [13][14][15] as well as in patients with portal hypertension. 16,17 It has been hypothesized that postprandial hyperemia may acutely augment portal pressure, and by this mechanism may probably increase the risk of bleeding from gastroesophageal varices.…”
mentioning
confidence: 99%
“…Cholinergic nerves play a role in postprandial hyperemia 36) , and beta adrenoreceptors form part of a humoral mechanism 37) . The effects of these nervous activities on vasodilation in the gastrointestinal tract are relatively small.…”
Section: Effect Of Food Ingestion On the Gastrointestinal Tract At Rementioning
confidence: 99%